Metaphor creation: A measure of creativity or intelligence? - Barros, Débora Pereira (2020)
The goal of the present study was to verify whether the “Metaphor Creation Test” would really be a measure with unique characteristics of creativity, or a different way of evaluating constructs already known as intelligence. Two differentiated groups were considered: group 1 was comprised by 90 late course students, and group 2 included 73 undergraduate students from Architecture and Urbanism courses. The results showed lower correlation between metaphors production and abstract reasoning (r= .31) comparing with verbal reasoning test (r= .48). Correlations between the constructs reproduced what was already found in other studies, that is, intelligence and creativity are related, but not strongly enough to affirm that they are the same construct; therefore they are different but related constructs.